Fabrication of tissue-engineered tympanic membrane patches using 3D-Printing technology. (February 2021) - Ilhan, Elif; Ulag, Songul; Sahin, Ali; Yilmaz, Betul Karademir; Ekren, Nazmi; Kilic, Osman; Sengor, Mustafa; Kalaskar, Deepak M.; Oktar, Faik Nuzhet; Gunduz, Oguzhan
Abstract: In recent years, scaffolds produced in 3D printing technology have become more widespread tool due to providing more advantages than traditional methods in tissue engineering applications. In this research, it was aimed to produce patches for the treatment of tympanic membrane perforations which caused significant hearing loss by using 3D printing method. Polylactic acid(PLA) scaffolds with Chitosan(CS) and Sodium Alginate(SA) added in various ratios were prepared for artificial eardrum patches. Different amounts of chitosan and sodium alginate added to PLA increased the biocompatibility of the produced scaffolds. The created patches were designed by mimicking the thickness of the natural tympanic membrane thanks to the precision provided by the 3D printed method. The produced scaffolds were analyzed separately for chemical, morphological, mechanical and biocompatibility properties. Scanning electron microscope (SEM), Fourier-transform infrared (FT-IR) spectroscopy was performed to observe the surface morphology and chemical structure of the scaffolds. Mechanical, thermal and physical properties, swelling and degradation behaviors were examined to fully analyze whole characteristic features of the samples. Cell culture study was also performed to demonstrate the biocompatibility properties of the fabricated scaffolds with human adipose tissue-derived mesenchymal stem cells (hAD-MSCs). 15 wt % PLA was selected as the control group and among all concentrations of CS and SA, groups containing 3 wt% CS and 3 wt% SA showed significantly superior and favorable features in printing quality. The research continued with these two scaffolds (3 wt% CS, and 3 wt% SA), which showed improved print quality when added to PLA. Overall, these results show that PLA/CS and PLA/SA 3D printed artificial patches have the potential to tissue engineering solutions to repair tympanic membrane perforation for people with hearing loss.